2018
DOI: 10.1126/science.aar3607
|View full text |Cite
|
Sign up to set email alerts
|

Defining the physiological role of SRP in protein-targeting efficiency and specificity

Abstract: The signal recognition particle (SRP) enables cotranslational delivery of proteins for translocation into the endoplasmic reticulum (ER), but its full in vivo role remains incompletely explored. We combined rapid auxin-induced SRP degradation with proximity-specific ribosome profiling to define SRP’s in vivo function in yeast. Despite the classic view that SRP recognizes amino-terminal signal sequences, we show that SRP was generally essential for targeting transmembrane domains regardless of their position re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
190
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(198 citation statements)
references
References 33 publications
8
190
0
Order By: Relevance
“…The latter observations led to the conclusion that yeast SRP is responsible for ER targeting of virtually all ribosomes synthesizing secretome proteins except for the tailanchored (TA) membrane proteins that are targeted by the GET pathway (17). However, rapid inactivation of yeast SRP combined with ER-specific ribosome profiling indicates that ribosomes synthesizing SRP-independent substrates remain ER-localized in SRPdeficient cells (18). In contrast, SRPdependent secretome proteins including integral membrane proteins are mistargeted to the mitochondria in SRP deficient cells (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter observations led to the conclusion that yeast SRP is responsible for ER targeting of virtually all ribosomes synthesizing secretome proteins except for the tailanchored (TA) membrane proteins that are targeted by the GET pathway (17). However, rapid inactivation of yeast SRP combined with ER-specific ribosome profiling indicates that ribosomes synthesizing SRP-independent substrates remain ER-localized in SRPdeficient cells (18). In contrast, SRPdependent secretome proteins including integral membrane proteins are mistargeted to the mitochondria in SRP deficient cells (18).…”
mentioning
confidence: 99%
“…However, rapid inactivation of yeast SRP combined with ER-specific ribosome profiling indicates that ribosomes synthesizing SRP-independent substrates remain ER-localized in SRPdeficient cells (18). In contrast, SRPdependent secretome proteins including integral membrane proteins are mistargeted to the mitochondria in SRP deficient cells (18).…”
mentioning
confidence: 99%
“…Allowing mecciRNA-bounded proteins to enter the mitochondria may even serve as a sorting mechanism to make sure the entry of right types and amounts of proteins and to keep unwanted cytosolic proteins and RNAs from entering the mitochondria. Interestingly, in a recent study, many proteins are found to demonstrate aberrant mitochondrial targeting in the absence of SRP that facilitates protein targeting to the endoplasmic reticulum (Aviram and Schuldiner, 2017;Costa et al, 2018;Walter and Blobel, 1982). There are also g-circRNAs encoded by the nuclear genome in the mitochondria ( Figure 1B), and it is also possible for them to play similar functions like mecciRNAs in mitochondrial protein importation.…”
Section: Discussionmentioning
confidence: 96%
“…This led to the concept that availability of ribosomes, aminoacyl-tRNA syntheases and charged tRNAs might be rate limiting and influence the speed of protein translation in one condition but not in another. 15 To test this possibility, we treated HEK293 cells with RO-3306, a CDK1inhibitor, which arrests cells in the G2 state [27]. The results from a flow cytometry analysis show that treatment with 7 µM RO-3306 caused the expected arrest of cells in G2 after 48 h of incubation (Fig.…”
Section: Sorting Is Affected By State Of the Cell Cycle But Not By Enmentioning
confidence: 99%
“…It is also possible that expression of Kesv reduces the amount of a ratelimiting chaperon like the signal recognition particle (SRP) [14], which is responsible for the correct sorting of the protein to the SP. Such a process could result in miss-sorting of a nascent protein [15]. To test this possibility we examined whether sorting of small K + channel proteins is generally compromised by codon bias.…”
Section: Mitochondrial Sorting Of Channel Protein Is Modulated By Codmentioning
confidence: 99%